2010
DOI: 10.1364/oe.18.013239
|View full text |Cite
|
Sign up to set email alerts
|

In-situ determination of astro-comb calibrator lines to better than 10 cm s^-1

Abstract: Improved wavelength calibrators for high-resolution astrophysical spectrographs will be essential for precision radial velocity (RV) detection of Earth-like exoplanets and direct observation of cosmological deceleration. The astro-comb is a combination of an octave-spanning femtosecond laser frequency comb and a Fabry-Pérot cavity used to achieve calibrator line spacings that can be resolved by an astrophysical spectrograph. Systematic spectral shifts associated with the cavity can be 0.1-1 MHz, corresponding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…1. A recently developed scanned cavity technique [16] can be used to identify and remove these systematic shifts from the final calibration which is critical since any dielectric mirror coating will contain both small errors and a systematic divergence of the dispersion at the edges of its working range.…”
Section: Spectral Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…1. A recently developed scanned cavity technique [16] can be used to identify and remove these systematic shifts from the final calibration which is critical since any dielectric mirror coating will contain both small errors and a systematic divergence of the dispersion at the edges of its working range.…”
Section: Spectral Filteringmentioning
confidence: 99%
“…Systematics of this calibration system including dispersion, higher order transverse modes of the cavity filter and alignment of the frequency comb and cavity filter transmission resonances have been characterized. Using a scanned-cavity technique [16], the accuracy of the astro-comb system has been compared to the underlying laser frequency comb. This type of broadband characterization of an astro-comb system is necessary to ensure that the optical filtering process has not left unevenly suppressed source comb lines on either side of each astro-comb line.…”
Section: Introductionmentioning
confidence: 99%
“…Several prototype astro-combs have recently been developed and tested with astrophysical spectrographs [5][6][7][8][9]11]. These tests have shown that the mode-filtering systems must be improved to provide adequate suppression of unwanted spectral lines ("side modes") in the presence of nonlinear processes in optical fibers.…”
mentioning
confidence: 99%
“…where f A is the astro-comb line frequency, δf A is the shift of the astro-comb line as measured on the spectrograph, I k is the intensity of the kth side mode (the source comb line k repetition frequencies away from the astro-comb line), and c is the speed of light [11,12]. To calibrate the spectrograph with an accuracy of 100 kHz with an astrocomb, the intensity of the side modes must be suppressed or controlled to <10 −4 of the astro-comb peak intensity [1,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation